PERLINDUNGAN KONSUMEN TERHADAP BEREDARNYA MAKANAN YANG TIDAK BERSERTIFIKAT HALAL - Sakti, Muthia; Ramadhani, Dwi Aryanti; Wahyuningsih, Yuliana Yuli (Jurnal Yuridis, 2015)
ndonesia as a Muslim-majority country needs an attention to food products which circulate freely. It is not just the attention of the medically healthy composition, but also should be noted that the food consumed is healthy and halal. Inclusion of halal labeling is basically mandatory or voluntary, but if there is a processed food business operators that produce and / or processed food to enter into Indonesian territory to be traded by claiming their products as halal, then the processed food business operators shall put halal labeling and responsible for halal products. It is intended that the right of consumers to correct information, clear and honest about the condition and guarantee of the goods and / or services can be appropriately and adequately protected. In this article, the author uses the method of normative juridical research. The purpose of this paper is to determine the validity of the Consumer Protection Act against halal labelingon food products for Muslim consumers.